(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The study was carried out to evaluate the release modification of indomethacin press coated tablets through different polymers. Several batches of press coated tablets were prepared with indomethacin and Avicel PH 102. The core tablet was compression coated with minimal compression pressure. Formulation IX was modified by incorporating PEG 6000, sodium chloride and sodium lauryl sulphate (SLS). In vitro dissolution studies of the formulations of different excipients were done at pH 7.2 in phosphate buffer using USP apparatus 2 (paddle method) at 50 rpm and 37 ± 0.5 °C temperature. The drug release data was treated in different mathematical fashion to identify the kinetic behaviour. It was found that, drug release which was inversely proportional to the amount of xanthan gum in the coating formulations was significantly changed by the polymers used in the study. Incorporation of SLS caused the drug to be released in near zero order fashion. Drug release was found to follow Higuchi mechanism for all the formulations. The study reveals that the polymers used may be a significant factor for the discrepancy in release rate of indomethacin. Bangladesh Pharmaceutical Journal 19(2): 219-225, 2016